2013
DOI: 10.3892/mmr.2013.1377
|View full text |Cite
|
Sign up to set email alerts
|

Levels of leptin and IL-6 in lungs and blood are associated with the severity of chronic obstructive pulmonary disease in patients and rat models

Abstract: Abstract. The aim of the present study was to compare leptin and interleukin (IL)-6 expression in patients and rat models with chronic obstructive pulmonary disease (COPD). Leptin and IL-6 levels were determined in patients with an acute exacerbation of COPD (AECOPD), stable COPD and in healthy controls. Rat models of COPD were developed, histological and immunohistochemical analyses were performed and leptin and IL-6 levels were determined. Leptin and IL-6 levels in the serum and sputum were higher in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
(22 reference statements)
1
18
3
3
Order By: Relevance
“…A number of pro-inflammatory cytokines, such as TNF-α, IL-4, IL-8, IL-1β, IL-6, IL-2, have been detected during COPD exacerbation and have been reported to be increased in both sputum and serum during COPD exacerbations [21-25]. In our study, levels of pro-inflammatory mediators in the Xuan Bai Cheng Qi group were lower than those in the control group.…”
Section: Discussioncontrasting
confidence: 47%
“…A number of pro-inflammatory cytokines, such as TNF-α, IL-4, IL-8, IL-1β, IL-6, IL-2, have been detected during COPD exacerbation and have been reported to be increased in both sputum and serum during COPD exacerbations [21-25]. In our study, levels of pro-inflammatory mediators in the Xuan Bai Cheng Qi group were lower than those in the control group.…”
Section: Discussioncontrasting
confidence: 47%
“…Meanwhile, Keatings et al36 reported that statistically significant increases of interleukin-8 and tumor necrosis factor-alpha were related to the severity of airway diseases. In a rat model, Liang et al37 reported that the frequency of acute exacerbation and severity of COPD were associated with a higher leptin level. Furthermore, oxidative stress is now recognized as a major predisposing factor in the pathogenesis of COPD 38.…”
Section: Discussionmentioning
confidence: 99%
“…10 Earlier, in smaller groups of patients (27 with acute exacerbation of COPD and 24 with stable COPD), opposite results were obtained: the serum levels in the exacerbation patients are significantly higher than in patients with stable COPD and healthy controls. 13 In other studies, however, no associations of blood leptin levels with the severity of COPD were found: such results were obtained in a large population-based study comprising 5175 controls and 1240 COPD patients of both genders from USA. 2 Only a few studies have explored the correlations of blood leptin levels with some lung function indexes of COPD patients.…”
Section: Discussionmentioning
confidence: 84%
“…12 Studies further suggest a significant impact of leptin on specific respiratory diseases, including obstructive sleep apnea, hypopnea syndrome, asthma, COPD and lung cancer. 2,[5][6][7][8][9][10][11]13 However, as new investigations are under way, the picture is becoming more complex. 12 In this respect we aimed to explore the possible role of serum leptin levels as biomarkers in COPD.…”
Section: Introductionmentioning
confidence: 99%